Danske minder i Island: Om mødet mellem dansk og islandsk kultur - Hauksdóttir, Auður (Danske Studier, 2011)
Throughout their long common history, contact between Denmark and Iceland was close and multifaceted. Copenhagen, in particular, was of central importance for Iceland’s history. It was here that the Icelanders had to negotiate with the Danes concerning their various interests, both of worldly and spiritual nature, and the University of Copenhagen was the most important seat of learning for Icelanders until the establishment of the University of Iceland in 1911. In addition, many Icelanders headed for Denmark to learn a trade or seek other practical training. The earliest signs of villages developing can be seen in Iceland at the end of the eighteenth century, first in the leading trading locations, and soon Reykjavík would emerge as the country’s leading town. Here an environment developed where Danish merchants and Danicised officials dominated, and where Danish culture and language were prominent. The lifestyle, clothing and behaviour of thisinfluential group set the trend for society, creating a chasm between the imported urban culture and established Icelandic rural traditions. Danish culture has therefore in numerous ways placed its stamp on Icelandic culture and for some time Danish was a major influence on the development of the vocabulary of Icelandic.